EPC/TURNKEY CONTRACT, LUMPSUM FIXED PRICE SUBJECT TO ADJUSTMENTS - Sarwono Hardjomuljadi (Universitas Muhammadiyah Jakarta, 2015)
The most important thing before starting the construction project is deciding the type of contract will be used for the project’s implementation. In order to get the proper decision, the understanding on various conditions of contracts are required. In Indonesia there are many project using the so called “modified” FIDIC Conditions of Contract for EPC/Turnkey Project, but with the incorrect understanding on the reasons of using EPC/Turnkey Contract, so instead of solving the problem it may caused bigger problems in practice, many problems raised during the execution due to such incorrect understanding of the spirit of EPC/Turnkey Contract. Most of Employers, in this case the government institution or state owned enterprises in Indonesia, choose the EPC/Turnkey Contract with minimum understanding of the essence of the EPC/Turnkey Contract. Their reasons of choosing the EPC/Turnkey Contract was the “tied schedule” and the “higher certainty of cost”. FIDIC EPC/Turnkey Contract based on the discussion in this paper, instead of fit the Employer’s need only, the EPC/Turnkey Contract still give chance to the contractor to submit their claim (Clause 20) and even the price is fixed, payment could be made once the claim is accepted (Sub-Clause 17.4) means that additional to the contract price can be done. One of the important noteworthy thing is that if there is additional cost it should be “added to the contract price”, while in the conventional contract it should be “included in the contract price”, so the final price will be the same (Sub-Clause 14.1). Keyword: EPC/Turnkey Contract, tied schedule, higher certainty of cost, added, included.